2022
DOI: 10.1364/oe.452548
|View full text |Cite
|
Sign up to set email alerts
|

Phase-locking dynamics of a 2D VCSEL hexagonal array with an integrated Talbot cavity

Abstract: In this paper, phase-locking dynamics of 2D VCSEL hexagonal array with an integrated Talbot cavity are numerically investigated based on rate equations aiming at achieving high brightness output. The processes of wavelength synchronization and phase locking under different fill factors ff and fractional Talbot cavity lengths L were addressed comprehensively. Different supermodes of phase-locked VCSEL array were then analyzed from both near-field and far-field pattern, and proved to be well matched with the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In other words, as long as the device operates in the single-mode regime, it appears that the devices are polarized along the [110] axis. However, as VCSEL becomes multi-mode, the dominant polarization direction starts to switch from [110] to [1][2][3][4][5][6][7][8][9][10] direction. It can be deduced that the fundamental mode is mostly polarized along the [110] direction, while the higher order transverse modes are polarized orthogonally.…”
Section: Cw Measurement Results Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In other words, as long as the device operates in the single-mode regime, it appears that the devices are polarized along the [110] axis. However, as VCSEL becomes multi-mode, the dominant polarization direction starts to switch from [110] to [1][2][3][4][5][6][7][8][9][10] direction. It can be deduced that the fundamental mode is mostly polarized along the [110] direction, while the higher order transverse modes are polarized orthogonally.…”
Section: Cw Measurement Results Analysismentioning
confidence: 99%
“…Firstly, it can be observed that the VCSELs are polarized along the minor axis of the elliptical relief feature. For VCSEL with 4µm×5µm relief geometry, the VCSEL is initially polarized towards [1][2][3][4][5][6][7][8][9][10], and it switches abruptly toward [110] at 2.3mA, all while the device remains reliably single-mode at all bias currents. This polarization switching behavior can be explained by considering the effect of the mode filter geometry in dictating the dominant polarization direction toward [1][2][3][4][5][6][7][8][9][10].…”
Section: Cw Measurement Results Analysismentioning
confidence: 99%
See 3 more Smart Citations